2019
DOI: 10.3390/life9010004
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Analysis of the Bacterial Symbiont Dactylopiibacterium carminicum from the Carmine Cochineal Dactylopius coccus (Hemiptera: Coccoidea: Dactylopiidae)

Abstract: The scale insect Dactylopius coccus produces high amounts of carminic acid, which has historically been used as a pigment by pre-Hispanic American cultures. Nowadays carmine is found in food, cosmetics, and textiles. Metagenomic approaches revealed that Dactylopius spp. cochineals contain two Wolbachia strains, a betaproteobacterium named Candidatus Dactylopiibacterium carminicum and Spiroplasma, in addition to different fungi. We describe here a transcriptomic analysis indicating that Dactylopiibacterium is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…2A and B and 3A). Given that P. americana lacks endogenous pectinases, pectinolytic gut symbionts may be relied upon to supply the enzymes necessary for deconstructing this abundant dietary component, as observed in honey bees (Apis mellifera) and scale insects (Dactylopius coccus) (60,61). In B. thetaiotaomicron, dietary pectic glycans are degraded by PULs catabolizing galactan, arabinan, homogalacturonan (HG), and rhamnogalacturonan I (RGI) (8).…”
Section: P Americana Harbors New Cultivablementioning
confidence: 99%
“…2A and B and 3A). Given that P. americana lacks endogenous pectinases, pectinolytic gut symbionts may be relied upon to supply the enzymes necessary for deconstructing this abundant dietary component, as observed in honey bees (Apis mellifera) and scale insects (Dactylopius coccus) (60,61). In B. thetaiotaomicron, dietary pectic glycans are degraded by PULs catabolizing galactan, arabinan, homogalacturonan (HG), and rhamnogalacturonan I (RGI) (8).…”
Section: P Americana Harbors New Cultivablementioning
confidence: 99%
“…One OTU was assigned to D. carminicum (β-proteobacteria, family Rhodocyclaceae). So far, this bacterial species has only been reported in the scale insect species Dactylopius coccus (Hemiptera: Coccoidea: Dactylopiidae), where it has been described as a nitrogen-fixing symbiont [103,104]. Dactylopius coccus is now well established in Morocco where it ravages the plants of Opuntia ficus-indica.…”
Section: Plos Onementioning
confidence: 99%
“…In sapsucking insects, protease activity was found in guts and it was suggested that 'digestive proteolysis may be widespread in homoptera' (Foissac et al, 2002). In the carmine cochineal, Dactylopiibacterium showed increased expression of protease and peptidase genes in a gut metatranscriptomic analysis suggesting a bacterial origin of proteases in guts (Bustamante-Brito et al, 2019). Some herbivores have a specialized diet, for example koalas eat eucalyptus, pandas eat bamboos, tortoises eat cactus, Monarch butterfly pupas eat Asclepias and maguey red worms eat Agave cactuses and their microbiota serves to digest some of the particular substances or antimetabolites in their host plants.…”
Section: Endophytes In Animal Gutsmentioning
confidence: 99%
“…In sap‐sucking insects, protease activity was found in guts and it was suggested that ‘digestive proteolysis may be widespread in homoptera’ (Foissac et al , 2002). In the carmine cochineal, Dactylopiibacterium showed increased expression of protease and peptidase genes in a gut metatranscriptomic analysis suggesting a bacterial origin of proteases in guts (Bustamante‐Brito et al , 2019).…”
Section: Endophytes In Animal Gutsmentioning
confidence: 99%
See 1 more Smart Citation